Anaphylactic Transfusion Reaction in a Patient with Anhaptoglobinemia: The First Case in Korea - Kim, Hyunsoo; Choi, Jonghyeon; Park, Kyoung Un; Kim, Hyon-Suk; Min, Yoo Hong; Kim, Moon Jung; Kim, Hyun Ok (Annals of laboratory medicine, 2012)
Anaphylactic transfusion reactions are rare complications of blood transfusions. Anhaptoglobinemia, a condition that has high incidence in Asia, can cause allergic transfusion reactions or anaphylaxis in severe cases. A 50-yr-old Korean woman was diagnosed with relapsed acute promyelocytic leukemia. She developed thrombocytopenia during chemotherapy and an anaphylactic transfusion reaction on the 4th and 5th platelet transfusions immediately after the transfusion of the platelet concentrates was initiated. Blood analysis showed no detectable serum haptoglobin. We examined her genetic phenotype and detected anhaptoglobinemia, which occurs because of an allelic deletion in the Hp gene cluster. The presence of an antibody against haptoglobin was detected by performing ELISA. To prevent anaphylactic reactions, apheresis platelets were transfused after washing. Consequently, anaphylactic transfusion reactions did not develop. Here, we report the first case of anhaptoglobinemia causing anaphylactic transfusion reaction in Korea.